2009
DOI: 10.1021/ac9022956
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of the Förster Distance for Two Commonly Used Bioluminescent Resonance Energy Transfer Pairs

Abstract: Förster resonance energy transfer (RET) is the nonradiative transfer of energy from a donor to an acceptor fluorophore. The Förster distance (R(0)), being the fluorophore separation corresponding to 50% of the maximum RET efficiency (E(RET)), is a critical parameter for optimization of RET biosensors. Sensitive RET-based monitoring of molecular rearrangements requires that the separation of the donor and acceptor RET pair is matched to their Förster distance. Here, for the first time, we experimentally determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 24 publications
1
48
0
Order By: Relevance
“…The use of BRET pairs may also magnify this effect. The r 0 for the BRET pair used in BRET 2 experiments is 7.5 nm; the largest value reported for a resonance energy transfer pair used in biological studies (67); and, as shown in Fig. 6, the effect of protein density on FRET efficiency is greater for energy transfer pairs with larger r 0 .…”
Section: Discussionmentioning
confidence: 86%
“…The use of BRET pairs may also magnify this effect. The r 0 for the BRET pair used in BRET 2 experiments is 7.5 nm; the largest value reported for a resonance energy transfer pair used in biological studies (67); and, as shown in Fig. 6, the effect of protein density on FRET efficiency is greater for energy transfer pairs with larger r 0 .…”
Section: Discussionmentioning
confidence: 86%
“…The efficiency of energy transfer depends on the relative orientation of the donor and acceptor and the distance between them (Zacharias et al, 2000), so that absolute distances can not be measured. Experimentally determined Förster distance R 0 (distance at which the energy transfer efficiency is 50%) for BRET 1 and BRET 2 is 4.4 nm and 7.5 nm, respectively (Dacres et al, 2010). 7TMR transmembrane core spans ~40 Å across the intracellular surface (Palczewski et al, 2000), which makes BRET suitable to the study of dimerization.…”
Section: Interpretation Of Bret Results -Possible Drawbacksmentioning
confidence: 99%
“…where r is a distance between donor and acceptor, Förster radius R 0 depends on spectral overlap and dipole orientations yielding R 0 values of 4.4 nm for BRET 1 and 7.5 nm for BRET 2 (Dacres et al, 2010). E is an important parameter in interpretation of the BRET assays used for oligomerisation studies.…”
Section: Basic Assumptionsmentioning
confidence: 99%
“…The BRET 2 system is reported to produce much less light than the BRET H system due to the fact that quantum yield of coelenterazine 400a is two order of magnitude smaller than that of coelenterazine h. 18 However, because of its large Förster distance and spectral separation, 11 BRET 2 is ideally matched to the size of the thrombin biosensor. Accordingly, the BRET 2 -based thrombin sensor is a good option for validating the microfluidic setup and optical detection system for high sensitivity biosensing.…”
Section: Experimental a Materialsmentioning
confidence: 99%
“…[5][6][7][8][9][10] BRET 2 is ideally matched to the scale of many protein interactions and rearrangements due to its relatively long Förster distance but has relatively low luminance arising from the low quantum yield of the substrate oxidation. 11 Recently, we reported a microscope-based microfluidic system for BRET-based biosensing, 12 , we made two changes to the design of the detection system. First, we increased the volume of reaction that is optically sampled by incorporating a cylindrical chamber ("BRET reaction chamber"), perpendicular to the common direction of flow with a total volume of 2p ll.…”
Section: Introductionmentioning
confidence: 99%